Parental presence at anaesthesia induction: A systematic review. Issue 4 (7th June 2016) - Erhaze, Eunice K.; Dowling, Maura; Devane, Declan
Abstract : This systematic review assessed the effectiveness of parental presence for children undergoing surgical or diagnostic procedures under general anaesthesia (such as bronchoscopy, laryngoscopy and laparoscopy). Randomized and quasi randomized trials with healthy children scheduled for elective diagnostic and surgical procedures under general anaesthesia (age range 0–16 years) where the intervention was parental presence at anaesthesia induction were included. A comprehensive literature search was conducted using electronic databases and the reference lists of included studies. The Cochrane collaboration's tool for assessing risk of bias was used for assessment of risk of bias. The Review Manager software was used to analyse and synthesize data. A random‐effect meta‐analysis was used when there was evidence of clinical and/or statistical heterogeneity. Of the 102 citations identified, nine trials involving 1021 children were eligible for inclusion. Only four were sufficient to be included in the meta‐analysis. There was no statistically significant difference on average in the level of anxiety in children and their parents either at separation or at induction between children allocated to parental presence and those allocated to no presence, premedication or parental presence plus premedication groups. Significant debate still surrounds this issue, and future trials should focus on the use of reliable and validated tools in assessing outcome measures. Summary Statements: What is already known about this topic? Parental presence at anaesthesia induction is believed to facilitate smooth induction. However, parental presence can have an impact on the both child and parent behaviour if the intubation is difficult. In accordance with the family‐centred care paradigm, many institutions worldwide promote parental presence at induction. What this paper adds? This review provides further evidence that parental presence alone at anesthesia induction results in no statistically significant difference in the level of anxiety in both children and their parents either at separation or induction when compared with parental absence. Premedication is more effective than parental presence in reducing the level of anxiety in children at induction and the anxiety level of parents at separation. The implications of this paper for policy/practice/research/education: Future trials should focus on the use of reliable and validated tools to enable consistent reporting of outcome measures. Future trials should also consider the influence of parental presence at anesthesia induction on children at each developmental stage. Organizations can assist nurses in making informed decisions on parental presence at induction by developing written policies and providing in‐service educational programmes.